Do Chief Executive Officer (CEO) Characteristics Influence Financial Performance? - Anisya Ramadanti; Windu Mulyasari; Kurniasih Dwi Astuti (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine the effect of the characteristics of the Chief Executive Officer (CEO) on financial performance with earnings management as an intervening variable. CEO is proxied by the dummy variable, namely CEO duality, CEO tenure and CEO education. Financial performance is measured by Return on Assets (ROA) while earnings management uses the Modified Jones Model measurement. The research population includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. 46 companies uses in this research with total 230 sample data. This research use multiple regression and path analysis as the tools to analize. The results indicate that the CEO duality has negative significant effect on ROA, CEO tenure has no effect on ROA and CEO education has significant effect on ROA. Earnings management does not act as a mediator between CEO characteristics and three proxies for ROA.